2009
DOI: 10.1080/09585190902983421
|View full text |Cite
|
Sign up to set email alerts
|

Workforce motivation in Japan: an examination of gender differences and management perceptions

Abstract: As Japan enters the new century, pending workforce shortages -a function of low birth rates and an aging population -increase the need to address gender issues in organizations. Throughout the past four decades, the number of female workers in Japan has been growing, although full-time female participation in the Japanese workforce remains below the levels of some other industrialized nations. Despite the growing importance that the Japanese female labor force is expected to play, relatively little is known ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 36 publications
0
31
0
3
Order By: Relevance
“…As organizations move to seek competitive advantages, it is suggested that corporate training and business schools recognize ways to increase an individual's self-efficacy and use these approaches for grooming potential leadership and talent; the findings might suggest this is particularly important for females. For example, mentoring programs have been identified as helpful in preparing female employees for management roles (Worthley et al, 2009). Vicarious experience is relevant in building self-efficacy (MacNab and Worthley, 2008) and can influence self-efficacy through mentoring.…”
Section: Discussionmentioning
confidence: 98%
“…As organizations move to seek competitive advantages, it is suggested that corporate training and business schools recognize ways to increase an individual's self-efficacy and use these approaches for grooming potential leadership and talent; the findings might suggest this is particularly important for females. For example, mentoring programs have been identified as helpful in preparing female employees for management roles (Worthley et al, 2009). Vicarious experience is relevant in building self-efficacy (MacNab and Worthley, 2008) and can influence self-efficacy through mentoring.…”
Section: Discussionmentioning
confidence: 98%
“…Toutefois, encore aujourd'hui, le discours public continue souvent de suggérer qu'il est acceptable pour une femme de travailler seulement si elle accomplit « correctement » son rôle d'épouse et de mère (Dubuc 2009 ;Worthley et al 2009). D'ailleurs, le modèle de la femme au foyer (専業主婦 ou professional housewife), ne remonte qu'à la période de 高度経済成長, soit au développement accéléré de l'économie.…”
Section: La Promotion De La Diversité En Lien Avec L'emploi Des Femmesunclassified
“…While Worthley, MacNab, Brislin, Ito and Rose (2009) found that gender has an influence on motivation, Stettes and Zimmermann (2013) state that gender has a minimal influence on motivation as women are only slightly more motivated than men.…”
Section: Gender and Motivationmentioning
confidence: 99%
“…The differences in terms of power distance and uncertainty avoidance, and differences in terms of masculinity/femininity between South Africa and Germany may account for this. As previously mentioned, culture is defined within the context of this study as the personality of a region and incorporates objectives and the criteria of a particular group of people (Worthley et al 2009). …”
Section: Differences In Motivation Between South Africa and Germanymentioning
confidence: 99%
See 1 more Smart Citation